A longitudinal study of the creation methods used by entrepreneurs to develop new products and services. (22nd April 2020) - Sordi, José Osvaldo De; Nelson, Reed Elliot; Meireles, Manuel; Hashimoto, Marcos; Junior, Milton De Freitas Chagas
This paper presents a longitudinal study of the development of products and services (P/S) by entrepreneurs from the perspective of nine creation methods: copy, new product development, improvement, frugal innovation, adaptation, new combination, exaptation, nonaptation spandrels, and nonaptation junk. Our sample consisted of 51 entrepreneurs whose ventures had been operational for over 42 months in a recessive environment characterised by very high failure rates. Our informants provided perceptions of technological and commercial certainty for 180 P/S launches that they executed. We observed that the creation methods which involved higher levels of uncertainty, such as adaptation and new combination, were only employed later, after the first successful implementation of a new P/S. The initial trajectory of these entrepreneurs is typified by creation methods involving low commercial and technological uncertainty followed by some more complex and uncertain initiatives, but always preferring safer innovations. Aside from offering the entrepreneur greater control over the commercial and technological environment, this strategy provides greater financial security due to the returns generated by the first successful P/S launch. We also observed that entrepreneurs who developed new projects at the request of clients presented greater mastery and diversity of creation methods.